KARAKTERISTIK METODOLOGIS TAFSIR ISYARI: ANALISIS KOMPARATIF MAKNA BATIN DAN PERSPEKTIF ILMIAH PADA SURAH AR-RAHMAN 19-20 - Risko Ari Saputra; M. Syahbana Al Fatih; Muhammad Nazaruddin; Akhmad Dasuki (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study examines the characteristics of Sufi exegesis (tafsir sufi) as one of the approaches in interpreting the Qur’an that emphasizes inner (esoteric) meanings alongside the outward (exoteric) text. The problem addressed in this research is how Sufi interpretation develops, what sources and methods it employs, and how its position is understood within the broader tradition of Qur’anic exegesis. The research questions include: (1) how did Sufi tafsir emerge and develop historically, (2) what are the primary sources and methodological approaches used in Sufi interpretation, and (3) who are the major figures and what are their contributions to this field. This study uses a qualitative library research method by analyzing classical and modern literature related to Sufi tafsir. The findings indicate that Sufi exegesis originated as a response to excessive worldly orientation and aims to revive spiritual values through the purification of the soul. Its sources include the Qur’an, Hadith, teachings of earlier Sufis, and spiritual experiences such as kashf and ilham. Methodologically, it integrates bayani, burhani, and especially ‘irfani approaches, with emphasis on symbolic interpretation (isyari). Furthermore, Sufi tafsir is divided into nazari (philosophical) and isyari (practical-spiritual) forms. Despite criticism regarding subjectivity, Sufi exegesis contributes significantly by enriching the understanding of the Qur’an with deeper spiritual insights while maintaining harmony with its outward meanings.